Busy Period and Busy Cycle Distributions and Parameters for a Particular M/G/oo Queue System - Ferreira, M. A. M.; Andrade, M. A. P. (EasyChair Preprint Nº 7887, 2025)
Solving a Riccati equation a collection of service times distributions, very general, is determined. For it the M /G/oo queue busy period and busy cycle probabilistic study, very comfortable, is performed. In addition the properties of that distributions collection are deduced and also presented.